2019
DOI: 10.1177/0734242x19893018
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the co-firing characteristics of bamboo wastes and coal through cone calorimetry and thermogravimetric analysis coupled with Fourier transform infrared spectroscopy

Abstract: To evaluate the combustion characteristics of raw or torrefied bamboo wastes and coal blends, the co-firing process determined by cone and pollutant emission was investigated by thermogravimetric analysis coupled with Fourier transform infrared spectroscopy. The results showed that torrefaction improved the fuel properties of bamboo wastes. Torrefied bamboo had a lower volatile fuel ratio, H/C and O/C ratios, pollutant emission and a higher heating value. They further affected the co-firing process of raw or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…THR is the total heat released per unit area of a sample from the beginning to the end of combustion [33]. Combining the THR with the HRR allows for a more comprehensive evaluation of the combustion characteristics of materials [34].…”
Section: Combustion Performancementioning
confidence: 99%
“…THR is the total heat released per unit area of a sample from the beginning to the end of combustion [33]. Combining the THR with the HRR allows for a more comprehensive evaluation of the combustion characteristics of materials [34].…”
Section: Combustion Performancementioning
confidence: 99%
“…These results showed that PCaAl-LDHs effectively inhibited the combustion of bamboo scrimber and effectively improved the fire safety of the bamboo scrimber. The total heat release (THR) is a sum parameter describing the total heat release per unit area of a sample from the beginning to the end of combustion [20]. Combining THR with HRR can more comprehensively evaluate the combustion characteristics of the material [21].…”
Section: Flame Retardant Property Of Frbsmentioning
confidence: 99%
“…As can be seen from Figure 5b, during the whole combustion process, the THR of FRBS increased with the extension of time. Compared with the original, the THR of FRBS under different flame-retardant concentrations was reduced by 11.89% and total heat release (THR) is a sum parameter describing the total heat release per unit area of a sample from the beginning to the end of combustion [20]. Combining THR with HRR can more comprehensively evaluate the combustion characteristics of the material [21].…”
Section: Flame Retardant Property Of Frbsmentioning
confidence: 99%
“…The rate of waste accumulation in many regions of the world significantly exceeds the technological and economic possibilities for waste processing. The scale and high risk of environmental pollution determine the need for the developing waste-to-energy technologies in different countries ( Ninduangdee et al, 2020 ; Xiang et al, 2020 ). The current directions of these technologies are co-incineration, pyrolysis and gasification of various waste ( Medina Jimenez et al, 2019 ; Zhao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%